Edukasi Deteksi Dini Faktor Risiko Kehamilan dengan Skor Poedji Rochjati di Puskesmas C.H. Martha Tiahahu - Asih Dwi Astuti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The Maternal Mortality Rate (AKI) is still a problem for maternal and child health in Indonesia. The high maternal mortality rate shows that the health of mothers and children is still low. Risk factor detection is one of the efforts to capture how a mother in pregnancy has an influence on her health during pregnancy, childbirth and the postpartum period. The purpose of this service is to empower pregnant women in carrying out early detection of high risk of pregnancy to improve maternal and child health, in addition to helping partners (puskesmas) in efforts to detect early pregnancy risk. The service method is carried out by providing counseling and identifying risk factors with the Poedji Rochjati scorecard. This service was carried out on 14 pregnant women at the C.H. Martha Tiahahu Health Center. In the risk of pregnancy in the Low Risk Pregnancy (KRR) category with a score of 2 of 6.43% (6 pregnant women). In the pregnancy risk category with High Risk Pregnancy (KRT) with a score of 6 - 10 amounting to 7.50% (7 pregnant women). In the pregnancy risk category with Very High Risk Pregnancy (KRST) with a score of > 12 of 1.7% (1 pregnant woman).